PERFIL CLÍNICO-EPIDEMIOLÓGICO DA TUBERCULOSE NA POPULAÇÃO PRIVADA DE LIBERDADE EM MATO GROSSO DO SUL - Alves de Souza Almeida, Milene; Dias de Oliveira, Roberto; Carla Pivetta de Araujo , Rafaele; da Silva Santos , Andrea; Croda , Júlio; Ferreira Lemos , Everton (ANAIS DO ENIC, 2026)
-